Tantangan Implementasi IKD dalam Meningkatkan Pelayanan Administrasi Kependudukan di Kabupaten Rokan Hulu - Nurmaini Dalimunthe; Arli Ardianto; Khairunsyah Purba (Al-Manar Journal of Public Administration and Management, 2025)
This study examines the challenges associated with the implementation of the Digital Population Identity (IKD) in enhancing the quality of population administrative services in Rokan Hulu Regency. While IKD represents a digital innovation aimed at streamlining and expediting public service delivery, its adoption at the regional level continues to encounter significant obstacles. Employing a descriptive qualitative approach, this research utilized data collection methods including observation, interviews, and document analysis. The findings reveal that several key factors impede the effective implementation of IKD: low levels of public participation, limited digital literacy, the lack of access to mobile devices among the population, inadequate infrastructure, and the absence of mandatory regulatory frameworks. In light of these challenges, a comprehensive strategy is imperative—one that involves intensified public outreach, the provision of sufficient supporting facilities, and the establishment of clear and enforceable policies to ensure the successful realization of digital transformation in population administration services.